Variation of viscosity and crystallization properties of synthetic ferronickel waste slag with Al2O3 content. Issue 16 (15th August 2021) - Zhang, Tongsheng; Zhang, Hualong; Dai, Shifan; Huang, Daoyuan; Wang, Wanlin
Abstract: Ferronickel slag is a by-product in the production of Ni–Fe alloy, which can be used to produce mineral wool. The crystallization and viscosity of ferronickel slag have great influence on the production process of mineral wool. The crystallization properties and viscosity of three kinds of ferronickel slags with different Al2 O3 contents were investigated. It was studied by viscometer and high-temperature confocal scanning laser microscope (CSLM). The morphology and composition of crystals in the slag were characterized by field scanning electron microscope (FE-SEM) and energy dispersive spectrometer (EDS). The experimental results show that the crystallization process of molten slag conforms to the Johnson-Mehl-Avrami (JMA) crystallization kinetic model. With the increase of Al2 O3 content, the crystal size of ferronickel slag becomes smaller, the crystallization time increases, and the crystallization capacity decreases. The main crystallization product of No.1 and 2 slag is orthopyroxene, and the main crystallization product in No.3 slag is alumina. With the increase of Al2 O3 content, the transition temperature of ferronickel slag increases first and then decreases. The variation of viscosity is mainly related to the precipitation and growth of crystals, and is also affected by the type and the number of crystals.